THE EFFECTIVENESS OF CHARACTER BASED STUDENT WORKSHEET ON INCREASING HONESTY IN ELEMENTARY SCHOOL LEVEL - Sartono, Emmanuel Kus Eddy; Prasetia, Hendra; Wuryandani, Wuri; Fathurrohman, Fathurrohman; Suparlan, Suparlan (JMIE (Journal of Madrasah Ibtidaiyah Education), 2024)
This study aims to test the effectiveness of character-based student worksheets to increase honesty in Elementary School level for fourth grade elementary school students. This will have an impact on the lack of character of honesty. This research is a quasi-experimental study, with a non-equivalent pretest posttest control group design. This research involved one control class group, and one experimental class group. The research was conducted in class IV A and IV B  Elementary School in Yogyakarta city. Data collection instrument for the character variables of Honesty with a self-assessment scale, to measure the character of honesty. Data analysis used the Independent T Test statistic. The results showed that there were differences between the experimental class and the control class in terms of achieving the characters of honesty. The use of effective character-based worksheets on the honesty character of fourth grade elementary school students. This is evidenced by the results of the experimental class significance test of 0.047 greater than 0.05.